2016
DOI: 10.1182/blood.v128.22.1318.1318
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Study of L-Glutamine Therapy in Sickle Cell Anemia and Sickle β0-Thalassemia Subgroup Analyses Show Consistent Clinical Improvement

Abstract: Background: Sickle cell disease (SCD) is characterized by continuous oxidative stress through various mechanisms contributing to the pathophysiology and clinical course of sickle cell crises (SCC) and organ damage. L-glutamine is a precursor for the synthesis of essential metabolic redox cofactors including Nicotinamide Adenine Dinucleotide (NAD). Early studies have demonstrated that altered erythrocyte NAD redox potential was improved by oral L-glutamine therapy, suggesting that higher L-glutamine utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Enrolment in SCD trials remains challenging: a systematic review of 174 SCD interventional trials closed to enrolment showed that 57% of them terminated owing to lowenrolment 254 . However, the recent completion of a series of large, multicentre, multinational clinical trials demonstrate that the SCD patient and provider community are eager to collaborate with the pharmaceutical industry to find effective new treatments 146,147,151,253,255 . The prospects for new treatments in SCD has never looked better.…”
Section: [H2] Prevention Of Complicationsmentioning
confidence: 99%
“…Enrolment in SCD trials remains challenging: a systematic review of 174 SCD interventional trials closed to enrolment showed that 57% of them terminated owing to lowenrolment 254 . However, the recent completion of a series of large, multicentre, multinational clinical trials demonstrate that the SCD patient and provider community are eager to collaborate with the pharmaceutical industry to find effective new treatments 146,147,151,253,255 . The prospects for new treatments in SCD has never looked better.…”
Section: [H2] Prevention Of Complicationsmentioning
confidence: 99%
“…Treatment effect was independent of hydroxyurea use. 107 These data formed the basis for FDA approval in patients with SCD aged 5 years and older. Although L-glutamine is approved for all SCD types, the phase 3 study included only patients with HbSS.…”
Section: Targeting Downstream Conse-quences Of Hbs Polymerizationmentioning
confidence: 99%
“…Hydroxyurea is not effective in some patients and has significant safety concerns, including potential embryofetal toxicity and myelosuppression. L‐glutamine, recently approved, demonstrated only a modest effect in prevention of vaso‐occlusive crisis without improvement in haematologic parameters, and does not target the pathophysiologic mechanism of disease . Therefore, a chronic preventive treatment remains a serious unmet need.…”
Section: Introductionmentioning
confidence: 99%